Real-Time Drone Command Processing: A Large Language Model Approach for IoD Systems - Sezgin, Anıl; Boyacı, Aytuğ (Fırat University, 2025)
One of the most critical steps toward autonomous capabilities, where natural language instructions can be successfully converted into executable API calls, is integrating Large Language Models (LLMs) into the ecosystem of the Internet of Drones (IoD). This study introduces an end-to-end LLM-based framework for enhancing real-time drone operation and problem handling in intent recognition, parameter extraction, and ambiguity resolution. It has resorted to a spectrum of methodologies in the form of Retrieval-Augmented Generation (RAG) and customized fine-tuning specific to each domain, towards accurate command interpretation and successful API generation. This paper evaluates the performance of the model on a carefully designed dataset containing 1,500 commands for the different scenarios of IoD with an average BLEU score of 89.6 and a cosine similarity of 0.94. Optimization techniques, such as parallel processing and better query handling, reduced the latency of this system by 15%, with an average query processing time of 0.9 seconds. This work gives considerable importance to the scalability and flexibility of the system, which is quite crucial for applications in domains like disaster response, precision agriculture, and surveillance. Proposed LLM-based framework thus tries to bridge gap between human intent and drone execution for intuitive, reliable, and efficient IoD deployments.

Doğal dil talimatlarının yürütülebilir API çağrılarına başarıyla dönüştürülebildiği otonom yeteneklere doğru atılan en kritik adımlardan biri, Büyük Dil Modellerinin (LLM) İnsansız Hava Araçları İnterneti (IoD) ekosistemine entegrasyonudur. Bu çalışma, amaç tanıma, parametre çıkarımı ve belirsizlik çözümleme alanlarında gerçek zamanlı drone operasyonlarını ve sorun çözümünü geliştirmek için uçtan uca bir büyük dil modeli tabanlı çerçeve sunmaktadır. Çalışmada, her alana özgü doğru komut yorumlama ve başarılı API oluşturma için Retrieval-Augmented Generation (RAG) yönteminden yararlanılmıştır. Çalışma, IoD'nin farklı senaryolarını kapsayan ve 1.500 komuttan oluşan bir veri kümesi üzerinde modeli değerlendirmiştir. Elde edilen sonuçlara göre, modelin ortalama BLEU skoru 89,6 ve kosinüs benzerliği 0,94 olarak ölçülmüştür. Paralel işlem ve daha iyi sorgu işleme gibi optimizasyon teknikleriyle sistemin gecikme süresi %15 azaltılmış ve ortalama sorgu işleme süresi 0,9 saniye olmuştur. Bu çalışma, özellikle afet müdahalesi, hassas tarım ve gözetim gibi alanlarda uygulamalar için oldukça kritik olan sistemin ölçeklenebilirliğine ve esnekliğine büyük önem vermektedir. Önerilen LLM tabanlı çerçeve, böylece insan amacı ile drone uygulamaları arasında sezgisel, güvenilir ve verimli IoD dağıtımları için bir köprü kurmayı amaçlamaktadır.
Gerçek Zamanlı Drone Komut İşleme: IoD Sistemleri için Büyük Dil Modeli Yaklaşımı
Keywords: Natural Language Processing; Doğal Dil İşleme; Autonomous Agents and Multiagent Systems; Otonom Ajanlar ve Çok Yönlü Sistemler